2020
DOI: 10.1073/pnas.1907799117
|View full text |Cite
|
Sign up to set email alerts
|

Chitin perception in plasmodesmata characterizes submembrane immune-signaling specificity in plants

Abstract: The plasma membrane (PM) is composed of heterogeneous subdomains, characterized by differences in protein and lipid composition. PM receptors can be dynamically sorted into membrane domains to underpin signaling in response to extracellular stimuli. In plants, the plasmodesmal PM is a discrete microdomain that hosts specific receptors and responses. We exploited the independence of this PM domain to investigate how membrane domains can independently integrate a signal that triggers responses across the cell. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 55 publications
(74 reference statements)
2
94
2
Order By: Relevance
“…Rather, this response relies on the OsCEBiP orthologue AtLYM2 (Faulkner et al, 2013). Recently, it was demonstrated that, besides AlLYM2, these responses in the plasmodesmal plasma membrane require AtLYK4 and AtLYK5 as well, although only AtLYM2 and AtLYK4 could be detected in the plasmodesmal plasma membrane (Faulkner et al, 2013;Narusaka et al, 2013;Cheval et al, 2020). Collectively, these observations point towards the existence of dynamic changes in the localization, association, or mobility of these receptors in chitin perception complexes, and furthermore that different receptor complexes may exist at different subcellular localizations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rather, this response relies on the OsCEBiP orthologue AtLYM2 (Faulkner et al, 2013). Recently, it was demonstrated that, besides AlLYM2, these responses in the plasmodesmal plasma membrane require AtLYK4 and AtLYK5 as well, although only AtLYM2 and AtLYK4 could be detected in the plasmodesmal plasma membrane (Faulkner et al, 2013;Narusaka et al, 2013;Cheval et al, 2020). Collectively, these observations point towards the existence of dynamic changes in the localization, association, or mobility of these receptors in chitin perception complexes, and furthermore that different receptor complexes may exist at different subcellular localizations.…”
Section: Discussionmentioning
confidence: 99%
“…Although this receptor generally does not seem to act on the cell membrane, it was shown to mediate molecular fluxes in response to chitin in an AtCERK1-independent manner in plasmodesmata (Faulkner et al, 2013;Narusaka et al, 2013). Although the regulation of these molecular fluxes furthermore requires both AtLYK4 and AtLYK5, only AtLYM2 and AtLYK4 could be detected in the plasmodesmal plasma membrane (Cheval et al, 2020). Collectively, these findings underpin the occurrence of differentially composed chitin receptor complexes at different cellular locations in Arabidopsis.…”
Section: Tomato Chitin Receptors and The Assembly Of Receptor Complexesmentioning
confidence: 92%
See 3 more Smart Citations